Government Cooperation with Business Entities in the Procurement of Infrastructure based on the Presidential Regulation Number 38 Year 2015 Study Drinking Water Supply System (Spam) in Umbulan - Dwi Alfianto; Sabela Gayo (Budapest International Research and Critics University, 2021)
Development of infrastructure is necessary, the concept of Government Cooperation with Business Entities could be a solution, the rules of this concept is mutual cooperation. On the scheme of Government Cooperation with Business Entities, state-owned companies and private support each other in the fund and accelerate the growth of infrastructure. Government Cooperation with Business Entities also known as Public Private Partnership is the concept of collaboration in the construction of infrastructure that involve private parties, so that the main obstacle to infrastructure development in the setting up of funds and human resources are limited through the Government Cooperation with Business Entities is a good opportunity to overcome these obstacles. Government cooperation With Business Entities In the Procurement of the Infrastructure is regulated in Presidential Regulation No. 38 of 2015. Drinking Water Supply system (SPAM) Umbulan East Java is the first project in the water sector that utilizes the scheme of Government Cooperation with Business Entities. The problems in this article is about the concept of the program of Government Cooperation with Business Entities in the procurement of infrastructure, Government guarantees on infrastructure projects through the scheme of Government Cooperation with Business Entities and the implementation of Government Cooperation with Business Entities in the system of procurement of drinking water in Umbulan East Java based on presidential Regulation No. 38 of 2015.